Evaluation of Quiescent-Interval Single-Shot Magnetic Resonance Angiography in Diabetic Patients With Critical Limb Ischemia Undergoing Digital Subtraction Angiography: Comparison With Contrast-Enhanced Magnetic Resonance Angiography With Calf Compression at 3.0 Tesla. (February 2019) - Wei, Li-Ming; Zhu, Yue-Qi; Zhang, Pei-Lei; Lu, Hai-Tao; Zhao, Jun-Gong
Purpose: To assess the diagnostic performance of quiescent-interval single-shot magnetic resonance angiography (QISS-MRA) at 3 tesla in diabetic patients with critical limb ischemia (CLI) vs contrast-enhanced MR angiography (CE-MRA) using digital subtraction angiography (DSA) as the standard of reference.Method: Thirty-seven consecutive diabetic patients (mean age 71.8±7.2 years; 30 men) with CLI (Fontaine stage III–IV) underwent QISS-MRA and CE-MRA with calf compression; DSA was the standard. Image quality (5-point Likert-type scale) and stenosis severity (5-point grading) for QISS-MRA and CE-MRA were evaluated by 2 blinded readers in 1147 and 654 vessel segments, respectively. Per-segment and per-region (pelvis, thigh, calf) sensitivity, specificity, positive predictive value, and negative predictive value were calculated.Results: Image quality of QISS-MRA was lower compared with CE-MRA in the pelvic region (p<0.001 in both readers) and thigh region (p=0.033 in reader 1 and p=0.018 in reader 2), whereas in the calf region, the image quality of QISS-MRA was better than CE-MRA (p=0.009 in reader 1 and p=0.001 in reader 2). In segment-based analyses, there was no difference between QISS-MRA and CE-MRA in sensitivity [89.5% vs 90.3% in reader 1 (p=0.774) and 87.6% vs 90.6% in reader 2 (p=0.266)] or specificity [94.2% vs 92.9% in reader 1 (p=0.513) and 92.9% vs 92.9% in reader 2 (p>0.999)]. In region-based analyses, QISS-MRA and CE-MRA yielded similar sensitivity and specificity in all areas but the pelvic region for reader 2 (specificity 95.5% vs 84.8%, p=0.041).Conclusion: QISS-MRA performed very well in diabetic patients with CLI and was a good alternative for patients with contraindications to CE-MRA.